Kemas Ulang Informasi Tanaman Obat-Obatan bagi Suku Sakai di Daerah Riau - Efendi, Aidah Febriani; Nurizzati, Nurizzati (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
The purpose of this research are: (1) to explain what kind of medicinal plants for Sakai Tribe in Riau Region, (2) to describe how to repackage information about medicinal plants for Sakai Tribe in Riau Region. Data was   collected   through   observation   and   interview   with   Sakai   Riau Customary Chief and Sakai Riau indigenous house guard officer. The writing of this paper used qualitative descriptive method. Data obtained through observation and direct interviews with the Chief of Customs and community Sakai District Riau. Based on the research concluded the things as follows. First, the types of medicinal plants for the Sakai Tribe in Riau Region, consisting of 21 plants, Second, the way of repackaging the information of medicinal plants for the Sakai Tribe in Riau Region hasstages and the design of the book, the stages are: (1 ) Identifying user needs, (2) Collecting information and selection of information sources, (3) Selecting sources containing useful information values, (4) Evaluating the validity of information, (5) Meriview, analyzing, extracting information into information form Which is more efficient for the user, (6) repackage of information into a form appropriate to the needs of users of information, (7) Distributing information by means of promotion. The design of the book as a promotional material is: (1) Prepare the framework of writing, (2) Cover Making, (3) Preface, (4) Table of contents, (5) The content of the book, (6) Closing.Keywords: Information Repackaging, Medicinal plants, Sakai tribe, Riau